Online Interaction in Higher Education: Is There Evidence of Diminishing Returns? - Castaño-Muñoz, Jonatan; Sancho-Vinuesa, Teresa; Duart, Josep M. (International Review of Research in Open and Distributed Learning, 2013)
Online interaction is considered to be a key aspect of effective e-learning and improved academic achievement. However, few studies have examined how effectiveness varies with the degree of interaction intensity. Using data for 17,090 students from three Catalan universities, in this paper we study the productivity associated with five different levels of interaction intensity in learning. We also compare the results obtained for fully online education with those for face-to-face learning. The analyses show that interaction in online education has diminishing returns, while in face-to-face learning it does not do so in a pure way. These results have implications for determining the optimum level of interaction that should be sought when designing courses and educational policies.